1998
DOI: 10.1021/ma970919b
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron Scattering and Dynamic Light Scattering from a Polyelectrolyte Solution:  DNA

Abstract: Static and dynamic properties of a DNA fragment of molecular weight 316 800 (contour length 1632 Å) in semidilute solutions are studied by small-angle neutron scattering (SANS) and static (SLS) and dynamic light scattering (DLS). SANS experiments in a solution with DNA concentration C p = 42 mg mL-1 were performed as functions of added salt concentration C s and temperature. The resulting plot of scattering intensity I(q) versus scattering wavevector magnitude q shows the existence of a broad peak whose positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
161
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(177 citation statements)
references
References 50 publications
16
161
0
Order By: Relevance
“…[10] Circular dichroism and UV absorption measurements were carried out with a Jasco J-715 spectropolarimeter. SAXS analysis was performed in a Kratky compact instrument provided by HECUS MBraun, Graz, Austria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Circular dichroism and UV absorption measurements were carried out with a Jasco J-715 spectropolarimeter. SAXS analysis was performed in a Kratky compact instrument provided by HECUS MBraun, Graz, Austria.…”
Section: Methodsmentioning
confidence: 99%
“…[10] An angular scan reveals a diffusive nature [11] for both modes (see the Supporting Information), the corresponding diffusion coefficients of which are reported in Table 1. The DLS data for micellar aggregates (lipid concenScheme 1.…”
mentioning
confidence: 99%
“…While there has been a number of DLS reports on the properties of DNA solutions (see, for example Refs. [71][72][73][74]), studies involving interactions between DNA and cationic amphiphiles are in a very limited number [18,24,75].…”
Section: A Dynamic Light Scattering Studymentioning
confidence: 99%
“…Such observations have been reported for different charged macromolecular systems, including synthetic [18][19][20][21][22] and biological polyelectrolyte solutions. [23][24][25] The fast mode is often interpreted as a process involving the diffusion of single polyions. 26 On the other hand, the occurrence and physical meaning of the slow mode is still not well understood, but various studies have shown that such processes or dynamics are related to the presence of aggregates or large domains in polyelectrolytes in the order of 100 nm.…”
Section: Introductionmentioning
confidence: 99%